Virulence Genes of Multi-drug Resistance Pseudomonas species Isolated from Milk and Some Dairy Products - Gamal, Heba; El-Diasty, Mohamed; Dapgh, Amany; El-Sherbini, Mohammed; El-Baz, Amira; Abdelkhalek, Adel (Journal of Advanced Veterinary Research, 2022)
Pseudomonas species is one of the psychotropic bacteria that can survive in low-tempered milk and dairy products besides producing heat-resistant spoilage enzymes. In this study, one hundred and fifty samples of milk and some dairy products were analyzed. The overall prevalence of Pseudomonas spp. was 44.66% (0% pasteurized milk, 16% butter, 20% pasteurized cream, 48.5% Talaga cheese, 50% bulk milk tank, 66.6% raw market milk, and 70% in raw cream). From 67 positive samples, eighty-three isolates were confirmed biochemically as Pseudomonas spp. The most prominent species were P. aeruginosa, then P. fluorescence, P. Fragi, P. psychrophile, P. proteolytica, P. alcaligens, P. lundensis, and P. brenneri by a percent of 38.5%, 37.5%, 10.8%, 6%, 2.4%, 2.4%, 1.2%, and 1.2%, respectively. Fourteen antibiotic discs were selected to measure the antimicrobial susceptibility of 59 isolates of Pseudomonas spp. The higher antimicrobial resistance was against Ampicillin (100%) followed by Colistin (98%), while the antibiotic sensitivity was higher against Imipenem (96.6%) then Meropenem (91.5%). The average MAR index of isolated Pseudomonas spp. was 0.462. Ten isolates of antimicrobial resistance serotypes of P. aeruginosa were O11: E, O8: C, O5: B, O4: F, and O2: B. Molecular identification of P. aeruginosa, P. fluorescence, and P. fragi was carried out using polymerase chain reaction (PCR) to determine their virulence genes (LasB, ExoS, pilB for P. aeruginosa, aprX for P. fluorescence and carA gene for P. fragi). High levels of antimicrobial-resistant (AMR) Pseudomonas spp.Â  threaten public health and cause global concern. The economic and public health impacts were discussed.